1D MoO3 Nanorods Decorated by Palladium Nanoparticles: Surface Plasmon Resonance Promoted Photodegradation of Congo Red Dye - Parvathi, L.T.; Karuthapandian, S. (Asian Journal of Chemistry, 2020)
In this work, 1D, MoO3 palm leaf shaped nanorods decorated by palladium nanoparticle for the photodegradation of organic pollutant. The Pd loaded MoO3 ratio were optimized and 2% Pd loaded MoO3 shows excellent photodegradation towards the organic pollutants. The synthesized Pd decorated MoO3 nanorods were characterized by various analytical tools such as TEM, SEM, BET, EDX, XRD, UV-DRS etc., The TEM and SEM results revealed that the palm leaf shaped MoO3 nanorods was well decorated by Pd metals. The crystallite size of MoO3 was decreased when increases the palladium loading percentage. The surface area of MoO3 lowered when palladium loaded. The prepared nanocomposites were in high purity confirmed by EDX analysis. The energy gap tailored into visible region by loaded palladium. The catalytic efficiency of the prepared nanocomposites were tested against the photo degradation of organic pollutant within 60 min and rate constant also calculated. The catalyst was not much lower their activity even five reusability. The OH− and h+ (holes) were the active species involved in the photodegradation mechanism.